Dragon kingdom of Wrenly. Book 9, Legion of lava - Quinn, Jordan (Quinn, Jordan. Dragon Kingdom of Wrenly, 2023)
"Cinder has left to find the truth about Villinelle, while the others are on the hunt for Valos, the evil wizard who is out to destroy all of dragonkind with beasts born from the fiery depths of Crestwood."--